Teknologi Disk Mill dan sistem Dry Home pada peternak itik petelur di Cambajawa Desa Baruga Kecamatan Bantimurung Kabupaten Maros - Mukhlisin Mukhlisin; Irvawansyah Irvawansyah (Universitas Negeri Makassar, 2019)
The Community Partnership Program (PKM) partners are laying eggs duck farmers in Cambajawa, Baruga Village, Bantimurung, Maros. The problems are: (1) lack of knowledge in application of animal feed processing technology; (2) lack of skills in application of animal feed processing technology; and (3) animal feed production still relies on the weather. The external target is a grinding machine (Disk Mill) for the manufacture of animal feed and a drying system (Dry Home). The methods used are: speechs, demonstrations, discussions, questions and answers, and assistance. The results achieved were (1) partners have knowledge in application of animal feed processing technology, (2) partners have skills in application animal feed processing technology; and (3) partners can produce animal feed without relying on the weather.